Psychiatric Power - Foucault, M. author. aut Link
XXIV, 383 p.
Keywords: In this new addition to the Collège de France Lecture Series Michel Foucault explores the birth of psychiatry, examining Western society's division of 'mad' and 'sane' and how medicine and law influenced these attitudes. This seminal new work by a leading thinker of the modern age opens new vistas within historical and philosophical study.